The First Eocene Species of the Genus Cryptophagus (Coleoptera, Clavicornia, Cryptophagidae - Lyubarsky, G.Yu.; Perkovsky, E.E. (Вестник зоологии, 2012)
Based on a fossil specimen from the Late Eocene Rovno amber (Ukraine), Cryptophagus harenus Lyubarsky et Perkovsky, sp. n., an Eocene species of this genus is described. The new species is similar to the extant desert species Cryptophagus desertus Lyubarsky and C. recticollis Solsky, differing by the large callosity occupying 1/4 length of lateral margin of pronotum. Из позднеэоценового ровенского янтаря (Украина) описан Cryptophagus harenus Lyubarsky et Perkovsky, sp. n. — первый эоценовый вид рода. Вид наиболее близок к современным пустынным видам Cryptophagus desertus Lyubarsky и C. recticollis Solsky; отличается от них большой мозолью, занимающей четвертую часть длины переднеспинки.